Toxicidade e expressão gênica em abelhas do gênero tetragonisca após a contaminação com agrotóxicos - Stuchi, Ana Lúcia Paz Barateiro (2009)
The goal of this study was to evaluate alterations on the gene expression of Tetragonisca bees after contamination with pesticides to subsequently use these insects as insecticide bioindicators. For that purpose, the LC50 and the concentration-mortality correlation were initially estimated for the insecticides in order to use sub-lethal concentrations in further analyses. Next, it was developed the biochemical characterization of the esterases to understand alterations due to contamination by pesticides. Finally, experiments were conducted to evaluate possible alterations in Tetragonisca workers by means of molecular markers. Molecular markers used were esterase isoenzymes and total protein; in addition, the technique of CEC (critical electrolyte concentration) was used to detect alterations in gene expression. The insecticides used were fipronil, malathion, neem and thiamethoxam. Tetragonisca angustula and Tetragonisca fiebrigi workers were collected from nests at the State University of Maringá. As for the biochemical characterization of the esterases, three regions were observed in T. fiebrigi: EST-1 (α-esterase, cholinesterase I), EST-2 (α-esterase, cholinesterase II) and EST-4 (αß-esterase, carboxylesterase) and in T. angustula two esterase regions were observed: EST-3 (α-esterase, acetylesterase) and EST-4 (αß-esterase, carboxylesterase). The EST-3 of T. angustula showed the highest thermostability, because its activity was detected up to 54°C, while in T. fiebrigi EST-1 and EST-2 were not detected above 52°C. In both species EST-4 is probably encoded by the same gene, and showed the same electrophoretic profile, inhibition and thermostability. The other esterases are species-specific: EST-1 and EST-2 were only observed in T. fiebrigi and EST-3 in T. angustula. This study supports the idea that the genus Tetragonisca consists of two species. The LC50 values showed a high toxicity by contact for fipronil in T. angustula (0.00053%) and T. fiebrigi (0.00062%). Regarding the esterases in T. angustula, it was observed partial inhibition of EST-3 and EST-4 by contact with the insecticide malathion at the 0.003% concentration and with thiamethoxam (0.1%), and only the EST-4 concentration 0.0025% with malathion. In the species where contamination occurred by ingestion, there was partial inhibition of EST-3 at 1% and EST-4 at concentrations of 1% and 2%. In T. fiebrigi it was detected an increase in the relative activity of EST-4 when the contamination was performed by contact with thiamethoxam (0.9%). In this species, when malathion was mixed with food, the concentrations of 0.2% and 0.45% caused partial inhibition of EST-4, but when the insecticide fipronil was used in the same concentrations, it was observed partial inhibition of EST-1 (0.0012%) in addition to EST-4. As for the analysis of total proteins, only T. fiebrigi showed reduced expression of p19 peptide (70-80 kDa) after contamination by contact with the insecticide malathion (0.0017%). For the neem insecticide, mortality was not observed in any of the species of bees at the concentrations used. In the analysis of CEC after contamination with malathion, different ways to modify the chromatin structure in T. fiebrigi were detected. Contamination by contact caused chromatin relaxation, indicating increased protein synthesis, while ingestion resulted in higher chromatin condensation. In T. angustula it was observed a slight alteration in the CEC value when the contamination occurred by ingestion. Thiamethoxam promoted the smallest alteration in chromatin structure of the two species in the contamination by ingestion. In the analysis of CEC after contamination with malathion by ingestion, evidence of apoptosis in cells of both species was detected, and in T. fiebrigi more cells with these characteristics were observed as well. The changes in the relative activity of esterases, total protein and chromatin structure lead to the conclusion that stingless bees T. angustula and T. fiebrigi could be used as indicators of the presence of the insecticides fipronil, thiamethoxam and malathion and the molecular markers used may become important tools for the detection of residues of these compounds in agroecosystems.